2007
DOI: 10.1002/hep.21800
|View full text |Cite
|
Sign up to set email alerts
|

Clevudine is highly efficacious in hepatitis B e antigen-negative chronic hepatitis B with durable off-therapy viral suppression

Abstract: A 24-week clevudine therapy was well-tolerated and showed potent and sustained antiviral effect without evidence of viral resistance in e-CHB patients. However, treatment for longer than 24 weeks would be needed to achieve durable remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
3
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 41 publications
0
108
3
3
Order By: Relevance
“…During 24 weeks of clevudine therapy, the rates of ALT normalization were 68.2% in patients with HBeAg-positive chronic hepatitis B 12 and 74.6% in patients with HBeAg-negative chronic hepatitis B. 13 Our data showed slightly lower rates of ALT normalization, specifically, 62.5% and 66.7% in the CHB/ HCC and CHB groups, respectively. In our study, 15 patients of the CHI/HCC group and 6 patients of the CHI group displayed normal ALT levels in a baseline study and they were excluded in the analysis of ALT normalization.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…During 24 weeks of clevudine therapy, the rates of ALT normalization were 68.2% in patients with HBeAg-positive chronic hepatitis B 12 and 74.6% in patients with HBeAg-negative chronic hepatitis B. 13 Our data showed slightly lower rates of ALT normalization, specifically, 62.5% and 66.7% in the CHB/ HCC and CHB groups, respectively. In our study, 15 patients of the CHI/HCC group and 6 patients of the CHI group displayed normal ALT levels in a baseline study and they were excluded in the analysis of ALT normalization.…”
Section: Discussioncontrasting
confidence: 46%
“…12,13 In our study, median changes in serum HBV DNA levels at 24 weeks in the CHB/HCC and CHB groups were -2.7 and -1.8 log 10 copies/mL, respectively. This relatively small reduction in serum HBV DNA levels may be due to reduced baseline DNA levels and higher rates of lower baseline ALT levels in our study population (Tables 1, 2), compared with those reported previously; 6.6-6.3 vs 8.29-6.92 log 10 copies/mL, 68.5% vs 31.8-26.4% ALT <2X ULN at baseline, respectively.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In humans, clevudine 10, 50, 100, or 200 mg/day for 28 days can reduce the median HBV DNA by -2.5, -2.7, -3, and -2.6 log 10 , respectively. More importantly, this suppression of antiviral activity is maintained at 12 and 24 weeks post-treatment [125][126][127][128].…”
Section: Clevudinementioning
confidence: 99%